A noncanonical role for Jagged1 in endothelial mechanotransduction - Suarez Rodriguez, Freddy; Virtanen, Noora; Kiviluoto, Elmeri; Driessen, Rob C. H.; Zhao, Feihu; Bouten, Carlijn V. C.; Stassen, Oscar M. J. A.; Sahlgren, Cecilia M. (Wiley, 2026)
The Notch signaling pathway plays a crucial role in regulating endothelial biology. Notch signaling is sensitive to hemodynamic forces and governs mechanically driven cardiovascular development, physiology, and remodeling. However, the mechanisms by which mechanical forces integrate with the Notch pathway remain largely unknown. Here, we uncover a noncanonical role for the Notch ligand protein jagged-1 (Jagged1) in regulating the activity of mechanosensitive kinases in endothelial cells. We show that shear stress induces expression and relocalization of Jagged1 to cell junctions downstream of flow. Jagged1 expression under stress demonstrates magnitude dependence, and peaks at 0.8–1 Pa without impacting the Notch-activation potential of Jagged1. Jagged1 also regulates the activity of mechanosensitive kinases. Deletion of Jagged1 reduces the activity of vascular endothelial growth factor receptor 2 (VEGFR2) and mitogen-activated protein kinase (ERK) in vitro and diminished ERK activity in zebrafish embryos without affecting canonical Notch signaling. Furthermore, direct physical stimulation of Jagged1 using antibody-conjugated beads triggers the activation of VEGFR2 and ERK, mediated by Jagged1-induced proto-oncogene tyrosine-protein kinase Src activation. Taken together, we demonstrate a previously unknown noncanonical role for Jagged1 as a regulator of the activity of pathways involved in endothelial mechanotransduction.